Overview of the Quality of Accommodation Services at Mina Hall Sukolilo Hajj Dormitory for Elderly Hajj Pilgrim During the Hajj Disembarkation Year 2024 : Case Report - Nabila, Hasna Fathin; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v2i0.3234, 2024)
The Ministry of Religious Affairs is responsible for providing various services for the Hajj pilgrims. The services provided including administrative, worship, health, and general services. The general services consist of accommodation and transportation which supposed to have good service quality to maintain public satisfaction. This case report aims to describe the quality of accommodation services at Mina Hall of Sukolilo Hajj Dormitory, Surabaya, for elderly pilgrim during the 2024 Hajj disembarkation period. Based on the findings, it was concluded that the accommodation quality at the Sukolilo Hajj Dormitory is good enough, though some facilities still need improvement to enhance service quality. It is recommended that Hajj Organizing Committee (Panitia Penyelenggara Ibadah Haji) have to conduct regular inspections of accommodations for pilgrims during transit, both at embarkation and disembarkation. These inspections should involve the facilities such as transit rooms and the amenities inside. This procedure aims to ensure that the hajj pilgrims, especially the elderly, have adequate facilities to support their more vulnerable health conditions and to provide comfort during transit. With these optimizations, it is expected that elderly-friendly services will improve the satisfaction and the comfort of elderly pilgrims.